Protection of Intellectual Property Rights in the Field of Television and the Internet. The Notion of Teleformat - Ульянова, Галина Олексіївна; Ульянова, Г. О.; Ульянова, Галина Алексеевна; Ulianova, Halyna O.; Бааджи, Наталія Пилипівна; Бааджи, Н. П.; Бааджи, Наталия Филипповна; Baadzhy, Nataliia P.; Подолєв, Олексій; Podoliev, Oleksii; Власюк, Денис Олегович; Власюк, Д. О.; et al. (Hemisferios University, 2021)
The article is devoted to the main issues of protection of intellectual property rights in the field of television and the internet, related to the spread of piracy in the field of copyright and related rights, and to the unlicensed copying of television broadcasts. Moreover, there is an emphasis on the exacerbation of existing problems in the context of the Covid-19 pandemic and how this affected the industry. This research considers international and national legislation in the field of intellectual law, international experience of various countries, approaches to theory, and problems of implementing existing measures, in order to propose some options for optimizing existing mechanisms. The research methodology use the following methods: formal-legal, historical-legal, comparative analysis, and modeling. The main issues under consideration are the following ones: international broadcasting regulation, the problem of uniform terminology, and prospects for the legal regulation of copyright in television broadcasting. The authors defend the uncompromising protection of intellectual property, highlighting the lack of basic definitions, to propose their own definitions, in order to avoid the weak copyright protection of television broadcasting organizations.

Стаття присвячена основним питанням захисту прав інтелектуальної власності у сфері телебачення та Інтернету, пов’язаним із поширенням піратства у сфері авторського права та суміжних прав, а також неліцензійного копіювання телевізійних передач. Крім того, акцент робиться на загостренні існуючих проблем у контексті пандемії Covid-19 та на тому, як це вплинуло на галузь. У цьому дослідженні розглядаються міжнародне та національне законодавство у сфері інтелектуального права, міжнародний досвід різних країн, підходи до теорії та проблеми впровадження існуючих заходів, з метою пропонування варіантів оптимізації існуючих механізмів. У методології дослідження використовуються такі методи: формально-правовий, історико-правовий, порівняльний аналіз, моделювання. Основними питаннями, які розглядаються, є: регулювання міжнародного мовлення, проблема єдиної термінології та перспективи правового регулювання авторського права в телевізійному мовленні. Автори відстоюють безкомпромісний захист інтелектуальної власності, підкреслюючи відсутність основних визначень, пропонують власні визначення, щоб уникнути слабкого захисту авторських прав телерадіомовних організацій.
Ulianova H. Protection of intellectual property rights in the field of television and the internet. The notion of teleformat / H. Ulianova, N. Baadzhy, O. Podoliev, D. Vlasiuk, H. Chumachenko // Ius Humani. Law Journal. - Vol. 10. - Issue 1. - Hemisferios University, 2021. – Р. 1-25.
Keywords: intellectual property law; television; Internet; television format; Covid-19; право інтелектуальної власності; телебачення; Інтернет; телевізійний формат; Covid-19; Research Subject Categories::LAW/JURISPRUDENCE